2001
DOI: 10.1523/jneurosci.21-11-03860.2001
|View full text |Cite
|
Sign up to set email alerts
|

Sparks and Puffs in Oligodendrocyte Progenitors: Cross Talk between Ryanodine Receptors and Inositol Trisphosphate Receptors

Abstract: Investigating how calcium release from the endoplasmic reticulum (ER) is triggered and coordinated is crucial to our understanding of how oligodendrocyte progenitor cells (OPs) develop into myelinating cells. Sparks and puffs represent highly localized Ca 2ϩ release from the ER through ryanodine receptors (RyRs) and inositol trisphosphate receptors (IP 3 Rs), respectively. To study whether sparks or puffs trigger Ca 2ϩ waves in OPs, we performed rapid high-resolution line scan recordings in fluo-4-loaded OP pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
60
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 82 publications
(68 citation statements)
references
References 76 publications
8
60
0
Order By: Relevance
“…The average width at half-maximal amplitude of puffs evoked by photolysis of caged IP 3 in Xenopus oocytes has already been reported to be 1.9 m (65). The size of puffs observed in various cultured cells (60) and oligodendrocytes (61) is similar to that observed in Xenopus oocytes despite the large difference in size of the cells. High resolution line scan imaging showed that Ca 2ϩ puffs in Xenopus oocytes arise as a result of Ca 2ϩ release from a fixed point source that is smaller than the limit of optical resolution (ϳ0.25 m) (66).…”
Section: Discussionsupporting
confidence: 68%
“…The average width at half-maximal amplitude of puffs evoked by photolysis of caged IP 3 in Xenopus oocytes has already been reported to be 1.9 m (65). The size of puffs observed in various cultured cells (60) and oligodendrocytes (61) is similar to that observed in Xenopus oocytes despite the large difference in size of the cells. High resolution line scan imaging showed that Ca 2ϩ puffs in Xenopus oocytes arise as a result of Ca 2ϩ release from a fixed point source that is smaller than the limit of optical resolution (ϳ0.25 m) (66).…”
Section: Discussionsupporting
confidence: 68%
“…Similar bursts of ryanodine-sensitive calcium transients have been observed in heart muscle (Cheng et al, 1993) in the presence of low concentrations of ryanodine and in oligodendrocyte progenitor cells (Haak et al, 2001) after application of 3,7-Dimethyl-1-propargylaxanthine (a caffeine analog). The triggering mechanism for SCaTs in our system is not yet known, although direct and indirect evidence allow us to rule out some possible mecha-nisms.…”
Section: Discussionsupporting
confidence: 57%
“…Ca 2+ sparks have been identified in cardiac, skeletal and smooth muscle cells (Bootman et al, 1995), where RyR2, RyR1 and RyR2/3 are predominantly expressed, respectively (Ogawa et al, 2002). In oligodendrocyte progenitors, Ca 2+ sparks and puffs have been recorded and cross-talk between RyR3 and IP3R2 is speculated (Haak et al, 2001). It has been suggested that IP3R2 is essential to induced Ca 2+ puffs and waves, while RyR3 generates the Ca 2+ sparks.…”
Section: Discussionmentioning
confidence: 99%